2018
DOI: 10.1136/bmjopen-2017-018284
|View full text |Cite
|
Sign up to set email alerts
|

Is palliative care support associated with better quality end-of-life care indicators for patients with advanced cancer? A retrospective cohort study

Abstract: ObjectivesThis study aimed to establish the association between timing and provision of palliative care (PC) and quality of end-of-life care indicators in a population of patients dying of cancer.SettingThis study uses linked cancer patient data from the National Cancer Registry, the electronic medical record system used in primary care (SystmOne) and the electronic medical record system used within a specialist regional cancer centre. The population resided in a single city in Northern England.ParticipantsRet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 25 publications
6
79
3
3
Order By: Relevance
“…One limitation was that we could not link our data to the various independent home hospice organizations in Singapore; hence, we could not examine the effect of timely referral and frequency of home hospice visits on ED utilization, shown to reduce ED utilization . The majority of dying cancer patients in Singapore receive community hospice services, and the high‐risk groups we found in our study may benefit from the early referral.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation was that we could not link our data to the various independent home hospice organizations in Singapore; hence, we could not examine the effect of timely referral and frequency of home hospice visits on ED utilization, shown to reduce ED utilization . The majority of dying cancer patients in Singapore receive community hospice services, and the high‐risk groups we found in our study may benefit from the early referral.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care involvement was associated with less aggressive care, as measured by the use of chemotherapy near death (odds ratio [OR], 0.34), intensive care unit admissions (OR, 0.12), emergency room visits (OR, 0.19), and hospitalizations near death (OR, 0.24); moreover, earlier palliative care was associated with better outcomes . Studies from Italy and the United Kingdom examining the effect of palliative care confirmed similar benefits with earlier referral …”
Section: Defining Key Elements Of Palliative Care Delivery: Team‐basementioning
confidence: 94%
“…The optimal timing of specialist palliative care referral remains unclear but likely depends on the individual patient and the health care system. In addition to a meta‐analysis suggesting that earlier referral was associated with a greater benefit, several nonrandomized studies have also demonstrated the impact of timely palliative care on aggressiveness of care at the end of life . In a retrospective cohort study, patients who were referred to a comprehensive cancer center more than 6 months before death were compared with those who were referred 6 months or less before death.…”
Section: Defining Key Elements Of Palliative Care Delivery: Team‐basementioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the Voices survey where only 18% of patients in community settings were likely to describe their pain as being completely controlled compared with 38% in hospital and 68% in hospice environments (VOICES National Survey of Bereaved People, ). Referral to palliative care is known to happen relatively late in the journey of a terminal cancer patient and one‐third of patients who die from cancer never receive specialist palliative care services (Ziegler et al., ). The idea of resilience of the patient to cope with problems has been found in other disease areas, not just palliative care (Fylan, Armitage, Naylor, & Blenkinsopp, ).…”
Section: Discussionmentioning
confidence: 99%